Bearing Behavior of the Fly Ash Deposits on Expressway - Chun-yu Cui; Shu-jian Wang; Wei Cui; Xiao Zheng (Advances in Civil Engineering)
The reinforcement treatment for embankment using the fly ash deposits as the filling material for roadbed was clarified in this paper. Studies have shown that fly ash can be used as the filling material for embankment, but the subgrade bearing capacity from the original fly ash deposits cannot meet the requirements for operating. Fly ash has a good condition to run the dynamic consolidation for meeting the requirements of embankment compaction. The modulus of resilience and the California bearing ratio (CBR) of fly ash is close to that of general filling material for embankment. Fly ash also has the engineering properties of high void ratio and low cohesion. The maximum level of compaction of the fly ash deposits can be 93% and the bear capacity can be about twice over before after the treatment.